1988
DOI: 10.1002/zoo.1430070304
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in the zoo population of the red panda subspecies Ailurus fulgens fulgens

Abstract: Genetic variation present in the global and regional zoo populations of the red panda is estimated by computer simulations. In this study it is demonstrated that inbreeding depression could occur on the short term in the regional populations. Migration between regional populations is recommended to ensure the future survival of the red panda in captivity. More genealogical lineages should be represented in the breeding program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…This technique has been applied to the analysis of allele survival in the populations of captive endangered wild animals (MacCluer et al. 1986; Princee 1988; Haig et al. 1990) and domestic animals (Rodriganez et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This technique has been applied to the analysis of allele survival in the populations of captive endangered wild animals (MacCluer et al. 1986; Princee 1988; Haig et al. 1990) and domestic animals (Rodriganez et al.…”
Section: Introductionmentioning
confidence: 99%
“…The procedure is quite simple; two unique alleles are assigned to each founder, and the genotypes of all descendants along the actual pedigree are generated through Monte Carlo simulation following Mendelian segregation rules. This technique has been applied to the analysis of allele survival in the populations of captive endangered wild animals (MacCluer et al 1986;Princee 1988;Haig et al 1990) and domestic animals (Rodriganez et al 1998;Toro et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Gene dropping has been applied to analyse allele survival in animal populations (MacCluer et al 1986;Princee 1988;Haig et al 1990;Toro et al 2000;Honda et al 2002) and to estimate the probability for the occurrence of homozygous lethal genotypes (LL) at any locus (Ballou 1997). However, only one study was found where gene dropping was used to estimate ancestral inbreeding ), but f a was not defined in the sense of Ballou (1997) as a cumulative proportion.…”
Section: Generationmentioning
confidence: 98%
“…Thus, our simple computational model of the animal breeding problem provides a novel, viable and robust approach to designing and comparing breeding strategies in captive populations. Our approach is different from the existing methodology for analysis of breeding strategies in that it does not follow a step-by-step process modeling the state of a population (such as gene dropping (Lacy, 1994;MacCluer et al, 1986;Princée, 1988) or pedigree simulation (Harris et al;Seal and Lacy, 1989)) but rather looks at any such process as an algorithm and uses algorithmic analysis techniques to evaluate and compare various strategies.…”
Section: Introductionmentioning
confidence: 99%